Feasibility Analysis of The Investment Project of Additional High Frequency Machinery in Increasing Production Capacity (JEM17: Jurnal Ekonomi Manajemen, 2023)
UD Berkah is a small business, that currently produces surface mats for adult slippers and children's slippers. Hot Embossing is one of a series of processes for making the surface of slippers. The Hot Embossing process requires a High Frequency machine to create a pattern on the printed slipper surface. Currently UD Berkah has 3 units of High Frequency machines to meet consumer demand. Due to the large number of requests, not all of them can be done by the company itself, so it requires the services of subcontractors to meet production shortages. Currently, the company plans to purchase High Frequency machines to overcome this problem. So it is necessary to analyze the feasibility of investment projects by considering several aspects with the Straight Line Depreciation method approach, Payback period, Net Present Value, Profitability Index and Internal Rate of Return. This is done to consider whether the investment in adding High Frequency machines is feasible or not for UD Berkah. Research results with an investment value of Rp. 55,000,000 with an economic life of 5 years, the results for a depreciation of Rp. 7,000,000 every year, NPV of Rp. 477,026,441, payback period results for 1 year and 8 months, Profitability Index value is 11.7, the IRR value shows the result of 37.54%, So it can be concluded that investing in high frequency machines is feasible. Keywords: Hot Embossing, High Frequency, Investment, Net Present Value, Internal Rate of Return.